Global Financial Development Report 2014 : Financial Inclusion - World Bank (Washington, DC, 2013)
Financial inclusion has become a major subject of interest among policymakers, researchers, and other financial sector stakeholders. Many countries, for example, have recently adopted explicit financial inclusion strategies with targets for financial inclusion. The interest reflects an increased recognition that financial inclusion can be a driver of economic growth and poverty alleviation, and that many individuals and firms are excluded unnecessarily from even basic financial services. About half of the world’s adult population— more than 2.5 billion people—have no bank account is one powerful example. Barriers such as cost, travel distance, and amount of paperwork and requirements play an important role. Many of these barriers can be addressed by better policies.